(untitled) (Communications in Computational Physics, 2023)
We propose a hybrid scheme combing the diffuse interface method and the material point method to simulate the complex interactions between the multiphase compressible flow and elastoplastic solid. The multiphase flow is modelled by the multi-component model and solved using a generalized Godunov method in the Eulerian grids, while the elastoplastic solid is solved by the classical material point method in a combination of Lagrangian particles and Eulerian background grids. In order to facilitate the simulation of fluid-solid interactions, the solid variables are further interpolated to the cell center and coexist with the fluid in the same cell. An instantaneous relaxation procedure of velocity and pressure is adopted to simulate the momentum and energy transfers between various materials, and to keep the system within a tightly coupled interaction. Several numerical examples, including shock tube problem, gas-bubble problem, air blast, underwater explosion and high speed impact applications are presented to validate the numerical scheme.